Calcium and magnesium in male reproductive system and in its secretion - SKANDHAN, K P; VALSA, J; TRIVEDI, B G; AMITH, S (The Indian Journal of Animal Reproduction, 2023)
Laboratory animals like rat (n=l0), guinea pig (n=a) and rabbit (n=l0) were selected for the study. Thereproductive organs and accessory glands were separated, weighed, homogenized and analysed for respectivelevels of calcium and magnesium. The level of calcium and magnesium were not same in all tissues of sameanimal species. H_igher levels of calcium were recorded from the secretions of corpus epididymis in rat and rabbit and from ventral prostrate glands of guinea pig. However, variable levels of magnesium were found in thesecretions of different organs of rat, rabbit and guinea pig.
Keywords: Male reproductiv~ system; Rat; Rabbit; Guinea pig; Calcium; Magnesium